2006
DOI: 10.1242/jcs.02985
|View full text |Cite
|
Sign up to set email alerts
|

Human Bcl-2 cannot directly inhibit the Caenorhabditis elegans Apaf-1 homologue CED-4, but can interact with EGL-1

Abstract: Although the anti-apoptotic activity of Bcl-2 has been extensively studied, its mode of action is still incompletely understood. In the nematode Caenorhabditis elegans, 131 of 1090 somatic cells undergo programmed cell death during development. Transgenic expression of human Bcl-2 reduced cell death during nematode development, and partially complemented mutation of ced-9, indicating that Bcl-2 can functionally interact with the nematode cell death machinery. Identification of the nematode target(s) of Bcl-2 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 68 publications
(81 reference statements)
1
20
0
Order By: Relevance
“…Yeast cells can be rescued from this growth arrest by the overexpression of mammalian antiapoptotic proteins, such as Bcl-x L , which leads to robust colony growth (32,51). Thus, in this well-established functional assay (23,29,37,76), the expression of Bak blocks yeast growth, which can be rescued by the overexpression of Bcl-x L (Fig. 3A, "on").…”
Section: Resultsmentioning
confidence: 98%
“…Yeast cells can be rescued from this growth arrest by the overexpression of mammalian antiapoptotic proteins, such as Bcl-x L , which leads to robust colony growth (32,51). Thus, in this well-established functional assay (23,29,37,76), the expression of Bak blocks yeast growth, which can be rescued by the overexpression of Bcl-x L (Fig. 3A, "on").…”
Section: Resultsmentioning
confidence: 98%
“…How, then, is Bcl-2, which acts by preventing MOMP, able to substitute for CED-9, whose antiapoptotic effect is exerted through sequestration of the nematode APAF-1 homolog CED-4? A more recent study 27 found that Bcl-2 does not interact with CED-4 in a yeast two hybrid screen; it does, however, interact with EGL-1. Furthermore, when the basic nematode apoptotic program is recapitulated in yeast, CED-9, but not Bcl-2, was able to prevent lethality caused by CED-3/CED-4 co-expression.…”
Section: Nematodes: Like Us Only Differentmentioning
confidence: 95%
“…The authors proposed that Bcl-2 prevents cell death in wild-type nematodes by binding EGL-1 through that protein's BH-3 domain, and that the ability of Bcl-2 to rescue the apoptotic phenotype of CED-9-deficient worms could be due to Bcl-2 preventing EGL-1 from neutralizing the small amount of maternally derived CED-9 present at the developmental stage at which the original experiments were performed. [26][27][28] Despite their frequent depiction as isolated, globular organelles, in healthy cells the mitochondria form a complex and interconnected network, subject to frequent fusion, fission, and remodeling events (reviewed in Hoppins et al 29 ). Imaging of mammalian cells undergoing apoptosis has revealed that mitochondria fragment during MOMP; subsequent studies have lent credence to the idea that mitochondrial dynamics and MOMP are intimately linked with increased mitochondrial fission leading to sensitivity to MOMP and increased fusion blocking or delaying it.…”
Section: Nematodes: Like Us Only Differentmentioning
confidence: 99%
“…2,19 The low affinity of EGL-1 for most mammalian pro-survival proteins, shown in the present study, is interesting in light of a recent report using a yeast model system. 20 Their data suggest Bcl-2 does not directly inhibit CED-4, as CED-9 does, but rather acts as a 'sink' to sequester EGL-1, preventing it from engaging CED-9. Our binding data would support this hypothesis provided the levels of Bcl-2 are sufficient to overcome its relatively low affinity (K D B10 mM) for EGL-1.…”
Section: Egl-1 Mutants Reveal Killing Thresholds Ef Lee Et Almentioning
confidence: 99%
“…2,19 More recently, studies employing yeast-based functional and other biochemical assays determined that in the nematode studies described above, Bcl-2 is probably functioning by binding to EGL-1 thereby preventing its association with CED-9. 20 However, although CED-9 appears able to prevent cellular processes such as mitochondrial fission in mammalian cells (suggesting potential interactions with mammalian proteins), 21 EGL-1 seems ineffective at inducing apoptosis. 21 We have also shown that mammalian BH3-only proteins such as Bim and Bad, unlike EGL-1, cannot dissociate CED-4:CED-9 complexes.…”
mentioning
confidence: 99%